The role of personal networks in the labour insertion of weak jobseekers. (2016) - Lamonica, Valentina; Ragazzi, Elena; Santanera, Elena; Sella, Lisa
This paper investigates the labour market outcomes of a representative sample of unemployed individuals attending regional vocational training programs in Piedmont, North-West Italy. In particular, it proposes a multivariate analysis to describe and assess the effects of individual social networks (family, friends and acquaintance) on trainees' employment outcome. Analysing the influence of different network configurations on the probability of getting employed in the post-training medium period, it can be pointed out that strict and intense family ties are negatively correlated to individual employability. Moreover, it emerges that job referral is one of the most popular job search channels among Italian trainees, proving to be the most successful one.